The Effect of Speed, Agility and Endurance on the Dribbling Ability of Club Putra Lintas Muara Bungo U15 Football Players - Prantori, Edo; Damrah, Damrah; Arsil, Arsil; Yudi, Alex Alda; Zarya, Fiky (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2023)
The purpose of the study was to determine the Effect of Speed, Agility and Endurance on the Dribbling Ability of Ssb Putra Lintas Muara Bungo U15 Football Players. The research method used in this study is a quantitative approach. The population in the study was SSB Putra Lintas Muara Bungo players who numbered 100 people. The sample was the age group of children (13-15 years) numbering 40 people. The sampling technique is Purposive Sampling. The instrument is to measure speed, a 20-meter running speed test, agility using a digging run, to measure endurance using a yoyo test, and to measure dribbling ability with a dribbling ability test. survey methods with measurement and test techniques, analysis techniques using a path analysis approach. Research results: 1) py1 path coefficient = 0.346 based on the results of the analysis obtained a calculated value greater than the ttable value, a value of 2.820 > 1.729 then in this case Ha is accepted and H0 is rejected which means the coefficient of path analysis is significant. 2) py2 path coefficient = 0.449 based on the results of the analysis obtained a calculated value greater than the ttable value, a value of 3.898 > 1.729 then in this case Ha is accepted and H0 is rejected which means that the coefficient of path analysis is significant. 3) py3 path coefficient = 0.784 based on the results of the analysis obtained a calculated value greater than the ttabel value, a value of 2.455 > 1.729 then in this case Ha is accepted and H0 is rejected which means the path analysis coefficient is significant. In conclusion, speed, agility, and endurance directly and significantly affect the dribbling ability of SSB Putra Lintas Muara Bungo U15 football players